Guía para la Aplicación de Marketing Experiencial, Publicidad Emocional y Odotipos para Generar la Experiencia de Marca en la Industria del Transporte Aéreo – Caso Lan Ecuador - Ortega Castro, Andrea Elizabeth (2012)
This thesis work was conducted with the aim of raising awareness of the different tools of marketing and advertising, in this case has been chosen the Odotipos as part of the experiential and emotional advertising, for this was carried out a help guide for the development of an advertising campaign through this tool focused to the aeronautical market Case LAN Ecuador. It h was investigated the communication objectives of LAN, what was expecting the consumer brand and its positioning, to find the best fragrance that can differentiate it from the other in an innovative manner. We identified the different steps to follow to create a odotipo and make it effective, coming to the conclusion that a campaign of Olfactory Marketing can be beneficial to a company because it reduces costs considerably, displacing traditional media more expensive as the television...